2009
DOI: 10.2353/ajpath.2009.090130
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Specific Deletion of Extracellular Signal-Regulated Kinase 2 Mitogen-Activated Protein Kinase Leads to Aberrant Cortical Collagen Deposition

Abstract: The mitogen-activated protein kinases extracellular signal-regulated kinase (ERK)1 and 2 are essential intracellular mediators of numerous transmembrane signals. To investigate neural-specific functions of ERK2 in the brain, we used a Cre/lox strategy using Nestin:Cre to drive recombination in neural precursor cells. Nestin:Cre;ERK2 fl/fl conditional knockout (cKO) mice have architecturally normal brains and no gross behavioral deficits. However, all cKO mice developed early-onset (postnatal day 35 to 40) fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…4), indicating that ERK2 may be required for regulation of astrogliosis. This is consistent with previous reports, which demonstrated that inhibition of the MEK-ERK pathway resulted in enhanced generation of astrocytes (Paquin et al, 2005;Samuels et al, 2008;Heffron et al, 2009). GFAP ϩ cells seem to be more abundant in outer layers than inner layers of cortices (Fig.…”
Section: Generation Of Erk2 Cko Micesupporting
confidence: 82%
See 1 more Smart Citation
“…4), indicating that ERK2 may be required for regulation of astrogliosis. This is consistent with previous reports, which demonstrated that inhibition of the MEK-ERK pathway resulted in enhanced generation of astrocytes (Paquin et al, 2005;Samuels et al, 2008;Heffron et al, 2009). GFAP ϩ cells seem to be more abundant in outer layers than inner layers of cortices (Fig.…”
Section: Generation Of Erk2 Cko Micesupporting
confidence: 82%
“…ERK is activated in social behavior circuits during resident-intruder aggression tests (Trainor et al, 2010). On the other hand, it was reported that mice with the deletion of ERK2 in the CNS (Heffron et al, 2009) did not exhibit prominent anomalies in behavior tests, although they did not perform social behavior tests. They used breeding pairs consisted of male nestin-creϩ; Erk2 flox/ϩ mated with female nestin-creϪ; Erk2 flox/flox mice: all mice in their study were borne and reared by control mothers.…”
Section: Discussionmentioning
confidence: 99%
“…the other known Erk), in cultured Erk2-null stem cells does not affect this outcome, the normal proliferation in Erk2 null mutants is unlikely due to Erk1 compensation. Studies of mice with an Erk deletion specifically in neural precursors have proven inconclusive (Heffron et al, 2009; Samuels et al, 2008; Satoh et al, 2007; Satoh et al, 2011). These data suggest that Erk is not essential in cell proliferation mediated by IGF signaling and/or other growth signaling.…”
Section: Igf Signalingmentioning
confidence: 99%
“…The role of ERK2 in neural development was studied by conditional deletion of ERK2 in neural precursor cells using the nestin promoter to drive Cre recombinase expression. Surprisingly, these mice developed grossly normal brain structures, and no behavioral abnormalities were initially detected (Heffron et al 2009). However, more detailed analysis revealed a decreased proliferation of neural progenitor cells at E15.5 and E17.5 resulting in a reduced number of astroglial cells, and thinning of cortical layers II/III.…”
Section: The Role Of Erk1/2 In Neurodevelopmentmentioning
confidence: 99%